Membangun Kualitas Pendidikan Melalui Kemampuan Literasi Dan Numerisasi Dalam Implementasi Kurikulum Merdeka - Dilla Nurfadillah; Firyal Nasywa Aufa; Ichsan Fauzi Rachman (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Education has become crucial in facing global challenges. By implementing the Merdeka Curriculum, it is hoped that students can develop their interests and talents to become excellent and creative successors of the nation. The purpose of writing this article is to provide an example of efforts in implementing the Merdeka Curriculum by enhancing students' literacy and numeracy skills. Using the literature review method, the author gathers several references from various relevant sources, resulting in efforts that can be used by: applying high-quality basic concepts, applying the basic concepts of the Sustainable Development Goals (SDGs), implementing the Merdeka Curriculum, and applying literacy skills. The aim is to explore how literacy and numeracy skills can be improved through the implementation of the Merdeka Curriculum.